1992
DOI: 10.1111/j.1475-097x.1992.tb00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute acidosis and alkalosis on leucine kinetics in man

Abstract: The effects of acute pH changes on whole body leucine kinetics (1-13C-leucine infusion technique) were determined in normal subjects. Plasma insulin, glucagon, and growth hormone concentrations were kept constant by somatostatin and replacement infusions of the three hormones. When acidosis was produced by ingestion of NH4Cl (4 mmol kg-1 p.os; n = 8) arterialized pH decreased within 3 h from 7.39 +/- 0.01 to 7.31 +/- 0.01 (P less than 0.001) and leucine plasma appearance increased by 0.13 +/- 0.04 mumol kg-1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…The study of Ballmer et al [14] confirmed that induced metabolic acidosis causes a negative nitrogen balance and a significant decrease in serum albumin synthesis. Furthermore, Reaich et al [15] found a significant increase in protein breakdown and amino acid oxidation after the ingestion of NH 4 CI for 5 days, findings confirmed by Straumann et al [16] but not by Nair et al [17]. In addition, a depression in muscle protein synthesis was observed after 2 days of metabolic acidosis in humans [18] and after 1 day in rats [19, 20].…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The study of Ballmer et al [14] confirmed that induced metabolic acidosis causes a negative nitrogen balance and a significant decrease in serum albumin synthesis. Furthermore, Reaich et al [15] found a significant increase in protein breakdown and amino acid oxidation after the ingestion of NH 4 CI for 5 days, findings confirmed by Straumann et al [16] but not by Nair et al [17]. In addition, a depression in muscle protein synthesis was observed after 2 days of metabolic acidosis in humans [18] and after 1 day in rats [19, 20].…”
Section: Introductionsupporting
confidence: 62%
“…Several studies have demonstrated the substantial influence ofpH on whole body protein turnover and muscle protein degradation [14,15,16, 36, 37], but only a few studies have investigated the impact of pH on muscle protein synthesis in vivo. Garibotto et al [21] showed, using the arterio-venous difference technique and a constant infusion of L -[ 3 H]phenylalanine, that CKD patients had significantly higher rates of both synthesis and degradation of muscle protein.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of long-chain fatty acids, unlike medium-chain triglycerides, also decreases leucine oxidation compared with controls (Keller et al 2002). In contrast, leucine oxidation is activated in healthy subjects by glucagon, (Pacy et al 1990) glucocorticosteroid therapy (Zimmerman et al 1989), and ammonium chloride-induced metabolic acidosis (Reaich et al 1992;Straumann et al 1992). Acute exercise induces activation of BCKD complex in human skeletal muscle, but after training the activity of this enzyme is reduced, along with an increase in BCKD kinase protein (Howarth et al 2007).…”
Section: Leucinementioning
confidence: 90%
“…Moreover, wasting of lean body mass is a common feature in patients with chronic uremic acidosis (13). The increase in whole body protein degradation reported in acute (14) and chronic (15) mineral acidosis in normal subjects might be an important pathogenic factor responsible for the loss of lean body mass in human uremia. In addition, the subjects with chronic mineral acidosis were also reported to exhibit a simultaneous increase in whole body protein synthesis and leucine oxidation in the post-absorptive state ( 15).…”
Section: Introductionmentioning
confidence: 99%